Diferença, simulacro e pensamento: a proposta do método de dramatização (Difference, simulacrum and thought: the proposal of the dramatization method) - Lobo, Amanda Souza Ávila (2021)
This article is configured as an attempt to present the perspective of thought present in the proposal of the dramatization method by Gilles Deleuze, which is done by a positive valuation of the idea of ​​difference and simulacrum. Therefore, we will present the Platonic considerations around the passage of time and the permanence, present in the theory of forms, that support the search for truth in the representative thought method, as well the criticisms of this model, made by the philosopher Gilles Deleuze under discussion contained in the appendix of the work “Logic of the sense” (1969), with its proposal of to reverse the Platonism. Then, we bring the text “The dramatization method” (1967) to extract from it the presentation of a new way of thinking that, based on the proposal of valuation the pure difference, breaks with a will to truth based on transcendent and moral foundations, and presents a condition of thought immanent to existence, valuing the body, its encounters and its experiences.